Orientasi dan Fungsi Kurikulum dalam Pendidikan - Mardiani Pane; Hery Noer Aly (Departement of Mathematics Education, 2023)
This study aims to provide information about the orientation and function of the curriculum in education. The type of research used in this research is library research. And the results of the research show that the orientations and functions curriculum in education are very comprehensive. First, cultural orientation, the results of the learning process in schools are expected to be able to inherit the cultural foundations of society to the next generations. Second, personal orientation, the results of the learning process are expected to equip students with the basic needs of individuals and groups. Third, vocational orientation, the results of the learning process can equip students to actively participate in the real world. Fourth, social orientation, the results of the learning process are expected to enable functional students in society to help create shared prosperity. Fifth, economic orientation, the results of the learning process carried out are also expected to enable individual student abilities to contribute the progressing of the nation/country as a whole.